2002
DOI: 10.3354/meps235205
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coastal pollution by combined determination of chemical and biochemical markers in Mullus barbatus

Abstract: Muscle concentrations of organochlorinated compounds as well as biliary levels of polycyclic aromatic hydrocarbon (PAH) metabolites were determined in red mullet Mullus barbatus as a sentinel species for assessing the pollution along the western Mediterranean coast. A battery of biochemical markers -biotransformation and antioxidant enzymes -were also measured in liver subcellular fractions to assess exposure to pollutants. Among them, 7-ethoxyresorufin O-deethylase (EROD) activity, as well as 7-penthoxyresoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…From the present study, information on parasites found in M. barbatus leads us to point out, as previously suggested by other authors (Porte et al, 2002;Zorita et al, 2008;Insausti et al, 2009), that M. barbatus is a suitable species for bioindicator analysis. The usefulness of the determination of H. fabri, Capillaria sp.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…From the present study, information on parasites found in M. barbatus leads us to point out, as previously suggested by other authors (Porte et al, 2002;Zorita et al, 2008;Insausti et al, 2009), that M. barbatus is a suitable species for bioindicator analysis. The usefulness of the determination of H. fabri, Capillaria sp.…”
Section: Discussionsupporting
confidence: 62%
“…that lead to high values compared to other areas of the Catalan coast (Eljarrat et al, 2001;Liquete et al, 2010;Palanques et al, 1998Palanques et al, , 2008Porte et al, 2002;Sánchez-Cabeza et al, 1999). Recent data from our laboratory on muscle samples of M. barbatus and C. linguatula from the Barcelona coast (unpublished data) confirm higher levels of organochlorine compounds than those from the Blanes coast, in agreement with the results of Porte et al (2002) in M. barbatus from the same areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our data suggest that the elevated CYP1A transcript levels were not related to the known metal pollution in Sfax, but to still uncharacterised organic pollutan(s). The correlation between individual levels of CYP1A and SOD transcripts may also be related to this putative environmental impact, as SOD is a classical marker for oxidative stress affected by many pollutants, both organic and inorganic (Bainy et al, 1996;Hansen et al, 2007;Peters et al, 1994;Porte et al, 2002).…”
Section: Discussionmentioning
confidence: 99%